High-toughness heat-treatment-free aluminum alloy and preparation method thereof
By optimizing the composition ratio and process of heat-free aluminum alloy, the flowability and sticking problems of large-size integrated die-cast parts have been solved, realizing a high-strength, high-toughness, and low-cost aluminum alloy material that is suitable for die-cast structural parts of new energy vehicles and meets green and low-carbon standards.
Patent Information
- Application Number
- CN202511145569.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-11-18
AI Technical Summary
Existing heat-free aluminum alloys have problems such as poor material fluidity and filling properties, uneven mechanical properties of castings, easy sticking to the mold during the die casting process, and product deformation after cooling in large-size integrated die casting parts. In addition, the raw material cost is high, energy consumption is large, and carbon emissions are high, making it difficult to meet the needs of green and low-carbon development.
By adjusting the composition ratios of Si, Fe, Cu, Mn, Mg, Ti, Sr, Cr, Sb, Sn, Ga, Hf, and RE, especially controlling the ratio range of M and N, the fluidity and filling performance of the alloy are optimized. Recycled aluminum is used as raw material, and trace elements Cr, Sb, Sn, Ga, Hf, and RE are added to improve strength and toughness. The quality of the castings is ensured through refining, degassing, and high-pressure die casting processes.
It achieves excellent fluidity and filling properties of high-strength and high-toughness heat-free aluminum alloy, with castings that do not stick to the mold, strong resistance to deformation after cooling, good corrosion resistance, reduced alloy cost, and compliance with green and low-carbon requirements. It is suitable for die-cast structural parts of large and medium-sized new energy vehicles.
Smart Images

Figure CN120967204A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of heat-free aluminum alloy materials, specifically relating to a high-strength and high-toughness heat-free aluminum alloy and its preparation method. Background Technology
[0002] Integrated die-cast body parts for new energy vehicles have been widely used. Compared with the traditional process of connecting multiple parts, the one-piece die-casting method achieves a high degree of integration, significantly reducing manufacturing costs and effectively improving the overall vehicle production efficiency. Among them, there is a consensus on developing heat-free aluminum alloys as a key material, such as Silafont-36, Castasil-37 aluminum alloys, C611 alloy, and heat-free alloys of Al-Si-Cu and Al-Si-Mg systems. The main characteristics of heat-free aluminum alloys are as follows: For example, Silafont-36 effectively improves the sticking problem by adding an appropriate amount of Mn element and reducing the Fe content, and improves the ductility, castability, process fluidity and weldability of the alloy by adding Sr element; Castasil-37 aluminum alloy adds a certain amount of Zr and Mo elements, while reducing the Mg content, which improves the castability of the alloy; in the invention patent with patent publication number CN113755722A, the yield strength of heat-free aluminum alloy can reach 130MPa and the elongation is greater than 10%; in the invention patent with patent publication number CN114411020A, the elongation of the non-heat-treated aluminum alloy reaches 10-15%.
[0003] With the widespread application of integrated die casting technology, some potential problems of heat-free aluminum alloys have gradually become apparent. In particular, large-size integrated die castings often suffer from poor material fluidity and product filling, uneven mechanical properties of castings, easy sticking to the mold during the die casting process, and product deformation after cooling. Moreover, most heat-free aluminum alloys currently developed use primary aluminum as raw material to produce aluminum alloys, which results in high material costs, high energy consumption, and high carbon emissions. Therefore, there will be a huge market demand for heat-free aluminum alloys that meet green and low-carbon requirements in the future. Summary of the Invention
[0004] The purpose of this invention is to provide a high-strength, high-toughness, heat-free aluminum alloy and its preparation method. The provided high-strength, high-toughness, heat-free aluminum alloy exhibits good fluidity and filling properties, excellent casting performance, and the casting does not stick to the mold during die casting, which helps improve the product qualification rate. After cooling, the casting has strong resistance to deformation and good corrosion resistance. After natural aging, it possesses high strength and high toughness, and stable product performance, making it suitable for die-cast structural components of large and medium-sized integrated new energy vehicles. This high-strength, high-toughness, heat-free alloy has high Fe tolerance and can be prepared using 100% recycled aluminum as raw material, significantly reducing the alloy manufacturing cost and aligning with the long-term development goal of green and low-carbon aluminum alloys.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] One of the technical solutions of this invention is to provide a high-strength and high-toughness heat-free aluminum alloy, which, in addition to Al, includes the following components by mass percentage:
[0007] Si: 6.8-9.3wt.%, Fe: 0.1-0.41wt.%, Cu: 0.01-0.24wt.%, Mn: 0.4-0.7wt.%, Mg: 0.08-0.55wt.% , Ti: 0.06-0.18wt.%, Sr: 0.016-0.041wt.%, Cr: 0.001-0.11wt.%, Sb: 0.001-0.01wt.%, Sn: 0.0 0.01-0.05 wt.%, Ga: 0.001-0.015 wt.%, Hf: 0.01-0.04 wt.%, and RE: 0.005-0.11 wt.%, wherein the total amount of impurities does not exceed 0.2 wt.%, and M = 100 × Sn / (Cr + Sb), 1 < M ≤ 2500, and N = 10 × RE / (Ga + Hf), 1 < N ≤ 100; the RE includes one or more of La, Ce, and Gd.
[0008] In the high-strength and high-toughness heat-free aluminum alloy of the present invention, the Si content is adjusted to reduce the coefficient of thermal expansion, thereby improving the alloy fluidity and filling performance. This ensures that the molten alloy can quickly and smoothly fill the end of complex, large or super-large casting units and poorly filled locations, ensuring the dimensional stability of the structural parts and reducing the occurrence of defects such as porosity and shrinkage cavities in the castings.
[0009] Most heat-free aluminum alloys have low Fe content (Fe content requirement is no more than 0.15%), while the high-strength and high-toughness heat-free aluminum alloy of this invention has a maximum Fe content of 0.41%, significantly improving the alloy's tolerance to Fe content. This invention can use recycled aluminum as raw material. The high Fe content of recycled aluminum itself reduces the tendency of die casting to stick to the mold, and using recycled aluminum as raw material also helps to improve the problem of heat-free aluminum alloys easily sticking to the mold. The disadvantage of high Fe content is a reduction in the alloy's elongation, mainly because Fe in the aluminum alloy matrix often forms lamellar or elongated iron-rich phases that cut through the matrix and disrupt the continuity of the alloy structure. Ti is a very effective grain refiner in aluminum alloys. Its function is to form a large number of Al3Ti particles in the aluminum matrix, increasing the crystal nuclei and promoting nucleation. It also improves the supercooling of the melt to achieve a grain refinement effect, thereby improving the alloy's strength and toughness.
[0010] In the high-strength, high-toughness, heat-free aluminum alloy of this invention, Cu mainly plays a solid solution strengthening role. Furthermore, it maintains the stability of the aging precipitates in the alloy, making the aged microstructure more dispersed and uniform, improving both strength and plasticity, and enhancing resistance to stress corrosion. Cu also reduces the potential difference between grain boundaries and within grains, alters the structure of precipitates, and refines grain boundary precipitates, thus improving the alloy's resistance to stress corrosion. Sr mainly acts as a modifier in the alloy, transforming the eutectic Si from a acicular structure to a fine granular or worm-like structure, and also refines α-Al.
[0011] Na is commonly found in aluminum ingots, and its content is even higher after remelting of scrap aluminum. Because Na has a low melting point and is almost insoluble in aluminum, it easily adsorbs onto dendrite surfaces or grain boundaries during solidification, forming NaAlSi compounds, leading to brittle cracking, or "Na embrittlement." Adding trace amounts of Sb to the matrix can generate Na3Sb compounds, allowing Na to form NaCl and be discharged into the slag. This invention adds trace amounts of Sb to the alloy system to minimize "Na embrittlement" and plays a crucial role in improving the alloy's toughness. Cr primarily has a microalloying effect, forming (CrFe)Al7 intermetallic compounds in the alloy system, hindering recrystallization nucleation and growth, thus improving the alloy's yield strength, toughness, and reducing stress corrosion cracking susceptibility. The dispersed distribution of Sn in the matrix also plays a microalloying role, effectively refining the alloy's grains. The fine precipitates formed enhance the hindering effect of dislocations during plastic deformation, thereby increasing the alloy's strength to a certain extent. The ratio of Sn, Cr, and Sb satisfies M = 100 × Sn / (Cr + Sb), where 1 < M ≤ 2500. This formula limits the ratio of Sn, Cr, and Sb to maximize the "synergistic optimization" effect. Within this range, the alloy exhibits optimal performance. The embodiments and comparative examples of this invention also demonstrate that if the alloying elements are outside this range, the mechanical properties of the alloy will decrease, meaning that the synergistic effect of the three elements is not manifested, and the advantages of each element are not maximized.
[0012] In this invention, rare earth compounds (RE) have a second-phase strengthening effect, effectively improving the strength and fluidity of the alloy. They also purify molten aluminum and reduce gas content during die casting. The addition of Mn increases strength and hardness, and works with Fe to reduce the alloy's tendency to stick to the mold. Mg mainly improves the alloy's yield strength and also enhances its fluidity and corrosion resistance. However, the addition of Mn and Mg can disrupt the uniformity of α-Al grain distribution in the matrix. Through repeated experiments, the inventors found that adding trace amounts of Ga to the heat-free alloy can significantly improve grain distribution. This is mainly due to its promoting effect on grain boundaries during the pre-crystallization stage, effectively reducing pre-crystallization phenomena and promoting the precipitation of the strengthening phase Mg2Si at the grain boundaries. The addition of trace amounts of Hf to the alloy exhibits excellent heterogeneous nucleation ability, resulting in significant grain refinement. Hf can also form Al3Hf in the alloy matrix. Al3Hf is a high-temperature stable compound that improves the alloy's heat resistance. Meanwhile, the inventors discovered in their research that when RE, Ga, and Hf are added to the alloy matrix, they not only exert their individual strengthening effects, but also interact synergistically to significantly increase the heterogeneous nucleation rate during solidification, greatly refine α-Al grains, inhibit the formation of pre-crystallized structures, and improve high-temperature resistance and the alloy's flow and filling properties. Controlling the content of RE, Ga, and Hf to satisfy N = 10 × RE / (Ga + Hf), 1 < N ≤ 100, maximizes the "synergistic optimization" effect. Within this range, the alloy exhibits optimal performance. The embodiments and comparative examples of this invention also confirm that if the alloying elements are outside this range, the mechanical properties of the alloy decrease, meaning the synergistic effect of the three elements is not manifested, and the advantages of each individual element are not maximized.
[0013] Preferably, the high-strength and high-toughness heat-free aluminum alloy, in addition to Al, further comprises the following components by mass percentage:
[0014] Si: 6.8-7.6wt.%, Fe: 0.36-0.41wt.%, Cu: 0.18-0.24wt.%, Mn: 0.4-0.7wt.%, Mg: 0.35-0.55wt. %, Ti: 0.06-0.18wt.%, Sr: 0.016-0.031wt.%, Cr: 0.005-0.11wt.%, Sb: 0.001-0.01wt.%, Sn: 0.0 0.01-0.035 wt.%, Ga: 0.009-0.015 wt.%, Hf: 0.01-0.04 wt.%, RE: 0.005-0.11 wt.%; wherein the total amount of impurities does not exceed 0.2 wt.%, and M = 100 × Sn / (Cr + Sb), 1 < M ≤ 2500, and N = 10 × RE / (Ga + Hf), 1 < N ≤ 100; the RE includes one or more of La, Ce, and Gd.
[0015] In the alloy composition ratio, by fine-tuning the composition range of certain key elements such as Si, Fe, and Mg, the composition of Si and Fe can be selected when there are different fluctuations in the composition in actual die-casting scenarios, so as to meet different application requirements and further improve the alloy performance.
[0016] More preferably, the high-strength and high-toughness heat-free aluminum alloy, in addition to Al, also includes the following components by mass percentage:
[0017] The composition is as follows: Si: 7.1 wt.%, Fe: 0.41 wt.%, Cu: 0.22 wt.%, Mn: 0.56 wt.%, Mg: 0.36 wt.%, Ti: 0.11 wt.%, Sr: 0.028 wt.%, Cr: 0.008 wt.%, Sb: 0.006 wt.%, Sn: 0.02 wt.%, Ga: 0.012 wt.%, Hf: 0.015 wt.%, RE: 0.09 wt.%, wherein the total amount of impurities does not exceed 0.2 wt.%, and the RE consists of La: 40 wt.% and Ce: 60 wt.%.
[0018] Preferably, the high-strength and high-toughness heat-free aluminum alloy, in addition to Al, further comprises the following components by mass percentage:
[0019] Si: 7.6-9.3wt.%, Fe: 0.1-0.35wt.%, Cu: 0.01-0.18wt.%, Mn: 0.4-0.7wt.%, Mg: 0.08-0.35wt.% , Ti: 0.06-0.18wt.%, Sr: 0.031-0.041wt.%, Cr: 0.001-0.005wt.%, Sb: 0.001-0.01wt.%, Sn: 0.0 35-0.05wt.%, Ga: 0.001-0.009wt.%, Hf: 0.01-0.04wt.%, RE: 0.005-0.11wt.%; wherein, the total amount of impurities does not exceed 0.2wt.%, and M = 100×Sn / (Cr+Sb), 1 < M ≤ 2500, and N = 10×RE / (Ga+Hf), 1 < N ≤ 100; the RE includes one or more of La, Ce, and Gd.
[0020] In the alloy composition ratio, by fine-tuning the composition range of certain key elements such as Si, Fe, and Mg, the composition of Si and Fe can be selected when there are different fluctuations in the composition in actual die-casting scenarios, so as to meet different application requirements and further improve the alloy performance.
[0021] More preferably, the high-strength and high-toughness heat-free aluminum alloy, in addition to Al, also includes the following components by mass percentage:
[0022] The composition is as follows: Si: 8.5 wt.%, Fe: 0.14 wt.%, Cu: 0.17 wt.%, Mn: 0.67 wt.%, Mg: 0.24 wt.%, Ti: 0.15 wt.%, Sr: 0.036 wt.%, Cr: 0.005 wt.%, Sb: 0.008 wt.%, Sn: 0.04 wt.%, Ga: 0.006 wt.%, Hf: 0.018 wt.%, RE: 0.08 wt.%, wherein the total amount of impurities does not exceed 0.2 wt.%, and the RE is composed of La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%.
[0023] The second technical solution of the present invention provides a method for preparing the above-mentioned high-strength and high-toughness heat-free aluminum alloy, comprising the following steps:
[0024] The raw materials are prepared according to the composition ratio of the high-strength and high-toughness heat-free aluminum alloy. All raw materials except Mg and Ga are melted, and then Mg and Ga are pressed into the melt for melting. The alloy is then successively refined and degassed, slag removed, composition detected and adjusted, and cast to obtain the high-strength and high-toughness heat-free aluminum alloy.
[0025] Preferably, the refining and degassing temperature is 720-740℃, and the amount of refining agent added during the process is 0.1-0.6% of the melt weight.
[0026] The third technical solution of the present invention provides an application of the above-mentioned high-strength and tough heat-free aluminum alloy in die-cast automotive parts.
[0027] Preferably, the die casting is high-pressure die casting, with a casting pressure of 350-450 bar, an injection speed of 3-6 m / s, a vacuum degree of <50 mbar, a die casting temperature of 680-720℃, and a mold temperature of 190-230℃.
[0028] The beneficial technical effects of the present invention are as follows:
[0029] The high-strength, high-toughness, heat-free aluminum alloy provided by this invention exhibits excellent fluidity, solving problems such as poor filling and poor mechanical properties at the distal end of large integrated die-cast structural parts, and also demonstrates high tolerance to Fe. The aluminum in this alloy can be entirely sourced from recycled aluminum. The resulting die-cast aluminum alloy in its Fe state exhibits a maximum tensile strength of 320 MPa, a maximum yield strength of 167 MPa, a maximum elongation after fracture of 17.6%, a maximum fluidity test result of 1150 mm, and a maximum bending angle of 41.6°. Compared to virgin aluminum, using recycled aluminum as a raw material reduces carbon emissions by 98.6%, significantly lowering manufacturing costs and better aligning with the long-term development goal of green and low-carbon aluminum alloys. Attached Figure Description
[0030] Figure 1 The image shows the metallographic structure of the product made using the aluminum alloy die-casting method of Example 3.
[0031] Figure 2 The image shows the metallographic structure of the product made using the aluminum alloy die-casting method of Example 5.
[0032] Figure 3 The image shows a scanning electron microscope (SEM) image of the fracture surface of the aluminum alloy die-cast product from Example 7 after it has been pulled apart.
[0033] Figure 4 The images show actual samples after bending angle testing of the aluminum alloy die-cast products from Examples 3, 5, and 7.
[0034] Figure 5 This is a physical image of a sample after a fluidity test was performed on the aluminum alloy die-casting product from Example 3. Detailed Implementation
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0036] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0037] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0038] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.
[0039] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0040] The raw materials used in the embodiments and comparative examples of this invention include: recycled aluminum, AlSi master alloy, AlFe master alloy, AlCu master alloy, AlMn master alloy, AlTi master alloy, AlSr master alloy, AlCr master alloy, AlSb master alloy, AlHf master alloy, Sn block, RE mixed rare earth block, Mg block and Ga block, which are formulated according to different embodiments and comparative examples.
[0041] Example 1
[0042] Preparation of heat-free recycled aluminum alloys:
[0043] S1. Material preparation and preheating: Prepare materials according to the components in Table 1, and place the prepared raw materials in a drying oven for preheating and drying.
[0044] S2. Alloy Melting: Set the furnace temperature to 740℃ and hold it at that temperature. Then, add the recycled aluminum raw material to the furnace, followed by AlSi master alloy, AlFe master alloy, AlCu master alloy, AlMn master alloy, AlTi master alloy, AlSr master alloy, AlCr master alloy, AlSb master alloy, AlHf master alloy, Sn block, and RE mixed rare earth (La: 50wt.%, Ce: 50wt.%). After melting, cool the furnace to 720℃. Use a bell jar tool to press the Mg block into the bottom of the crucible to melt it, preventing the Mg from burning on the liquid surface. Then, press the Ga block wrapped in aluminum foil into the bottom of the crucible to melt it.
[0045] S3. Refining, degassing and slag removal: Refining and degassing of the melt at 740℃, with the amount of refining agent added being 0.5% of the melt mass fraction, and the refining and degassing time being 10 minutes. After that, the slag produced during refining is removed and the mixture is left to stand for 15 minutes.
[0046] S4. Casting process: Casting a small sample of the composition for spectral analysis. After the composition is qualified, the alloy liquid is poured into the ingot mold and cooled to obtain a heat-free recycled aluminum alloy ingot.
[0047] S5. High-pressure die casting: The alloy ingot is subjected to high-pressure die casting. The relevant process parameters for die casting are set as follows: casting pressure 350 bar, injection speed 6 m / s, vacuum degree <50 mbar, die casting temperature 680℃, and mold temperature 190℃. The die casting product is an integrated die casting rear floor of a new energy vehicle body. The average thickness of this product is 3 mm.
[0048] Example 2
[0049] Preparation of heat-free recycled aluminum alloys:
[0050] The composition is shown in Table 1, in which the RE mixed rare earth is La: 40 wt.% and Ce: 60 wt.%, and the preparation steps are the same as in Example 1.
[0051] Example 3
[0052] Preparation of heat-free recycled aluminum alloys:
[0053] The composition is shown in Table 1, in which the RE mixed rare earth is La: 40 wt.% and Ce: 60 wt.%, and the preparation steps are the same as in Example 1.
[0054] Example 4
[0055] Preparation of heat-free recycled aluminum alloys:
[0056] The composition is shown in Table 1, in which the RE mixed rare earth is La: 55 wt.% and Ce: 45 wt.%, and the preparation steps are the same as in Example 1.
[0057] Example 5
[0058] Preparation of heat-free recycled aluminum alloys:
[0059] The composition is shown in Table 1, in which the RE mixed rare earth is La: 60 wt.% and Ce: 40 wt.%, and the preparation steps are the same as in Example 1.
[0060] Example 6
[0061] Preparation of heat-free recycled aluminum alloys:
[0062] The composition is shown in Table 1, in which the RE mixed rare earth is La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%, and the preparation steps are the same as in Example 1.
[0063] Example 7
[0064] Preparation of heat-free recycled aluminum alloys:
[0065] The composition is shown in Table 1, in which the RE mixed rare earth is La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%, and the preparation steps are the same as in Example 1.
[0066] Example 8
[0067] Preparation of heat-free recycled aluminum alloys:
[0068] The composition is shown in Table 1, in which the RE mixed rare earth is La: 55 wt.% and Ce: 45 wt.%, and the preparation steps are the same as in Example 1.
[0069] Example 9
[0070] Preparation of heat-free recycled aluminum alloys:
[0071] The composition is shown in Table 1, in which the RE mixed rare earth is La: 55 wt.%, Ce: 40 wt.%, and Gd: 5 wt.%, and the preparation steps are the same as in Example 1.
[0072] Example 10
[0073] Preparation of heat-free recycled aluminum alloys:
[0074] The composition is shown in Table 1, in which the RE mixed rare earth is La: 55 wt.%, Ce: 40 wt.%, and Gd: 5 wt.%, and the preparation steps are the same as in Example 1.
[0075] Comparative Example 1
[0076] Preparation of heat-free recycled aluminum alloys:
[0077] The composition is shown in Table 1, in which the RE mixed rare earth is La: 40 wt.% and Ce: 60 wt.%, and the preparation steps are the same as in Example 1.
[0078] Comparative Example 2
[0079] Preparation of heat-free recycled aluminum alloys:
[0080] The composition is shown in Table 1, in which the RE mixed rare earth is La: 40 wt.% and Ce: 60 wt.%, and the preparation steps are the same as in Example 1.
[0081] Comparative Example 3
[0082] Preparation of heat-free recycled aluminum alloys:
[0083] The composition is shown in Table 1, in which the RE mixed rare earth is La: 40 wt.% and Ce: 60 wt.%, and the preparation steps are the same as in Example 1.
[0084] Comparative Example 4
[0085] Preparation of heat-free recycled aluminum alloys:
[0086] The composition is shown in Table 1, in which the RE mixed rare earth is La: 40 wt.% and Ce: 60 wt.%, and the preparation steps are the same as in Example 1.
[0087] Comparative Example 5
[0088] Preparation of heat-free recycled aluminum alloys:
[0089] The composition is shown in Table 1, in which the RE mixed rare earth is La: 40 wt.% and Ce: 60 wt.%, and the preparation steps are the same as in Example 1.
[0090] Comparative Example 6
[0091] Preparation of heat-free recycled aluminum alloys:
[0092] The composition is shown in Table 1, in which the RE mixed rare earth is La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%, and the preparation steps are the same as in Example 1.
[0093] Comparative Example 7
[0094] Preparation of heat-free recycled aluminum alloys:
[0095] The composition is shown in Table 1, in which the RE mixed rare earth is La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%, and the preparation steps are the same as in Example 1.
[0096] Comparative Example 8
[0097] Preparation of heat-free recycled aluminum alloys:
[0098] The composition is shown in Table 1, in which the RE mixed rare earth is La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%, and the preparation steps are the same as in Example 1.
[0099] Comparative Example 9
[0100] Preparation of heat-free recycled aluminum alloys:
[0101] The composition is shown in Table 1, in which the RE mixed rare earth is La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%, and the preparation steps are the same as in Example 1.
[0102] Comparative Example 10
[0103] Preparation of heat-free recycled aluminum alloys:
[0104] The composition is shown in Table 1, in which the RE mixed rare earth is La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%, and the preparation steps are the same as in Example 1.
[0105] Comparative Example 11
[0106] Preparation of heat-free recycled aluminum alloys:
[0107] The composition is shown in Table 1, in which the RE mixed rare earth is La: 40 wt.% and Ce: 60 wt.%, and the preparation steps are the same as in Example 1.
[0108] Comparative Example 12
[0109] Preparation of heat-free recycled aluminum alloys:
[0110] The composition is shown in Table 1, in which the RE mixed rare earth is La: 50 wt.%, Ce: 40 wt.%, and Gd: 10 wt.%, and the preparation steps are the same as in Example 1.
[0111] Table 1. Composition of heat-free recycled aluminum alloys in each group (wt.%)
[0112] serial number Si Fe Cu Mn Mg Ti Sr Cr Sb Sn Ga Hf RE Al Example 1 6.8 0.35 0.21 0.65 0.55 0.15 0.030 0.060 0.008 0.015 0.013 0.020 0.101 margin Example 2 7.0 0.38 0.18 0.61 0.48 0.13 0.027 0.005 0.005 0.009 0.009 0.014 0.005 margin Example 3 7.1 0.41 0.22 0.56 0.36 0.11 0.028 0.008 0.006 0.020 0.012 0.015 0.090 margin Example 4 9.3 0.12 0.01 0.58 0.26 0.08 0.041 0.003 0.006 0.035 0.001 0.010 0.110 margin Example 5 7.6 0.28 0.19 0.53 0.35 0.15 0.032 0.110 0.001 0.037 0.008 0.012 0.087 margin Example 6 8.3 0.22 0.16 0.40 0.33 0.14 0.031 0.005 0.003 0.036 0.009 0.040 0.075 margin Example 7 8.5 0.14 0.17 0.67 0.24 0.15 0.036 0.005 0.008 0.040 0.006 0.018 0.08 margin Example 8 7.8 0.26 0.13 0.62 0.13 0.06 0.037 0.001 0.010 0.050 0.014 0.016 0.005 margin Example 9 8.0 0.10 0.15 0.49 0.08 0.17 0.033 0.005 0.007 0.042 0.008 0.033 0.006 margin Example 10 6.9 0.38 0.24 0.70 0.50 0.18 0.016 0.006 0.009 0.035 0.014 0.012 0.055 margin Comparative Example 1 7.1 0.41 0.22 0.56 0.36 0.11 0.028 0.008 0.006 0.020 - - 0.090 margin Comparative Example 2 7.1 0.41 0.22 0.56 0.36 0.11 0.028 0.008 - 0.020 0.012 - - margin Comparative Example 3 7.1 0.41 0.22 0.56 0.36 0.11 0.028 - 0.006 - 0.012 - 0.090 margin Comparative Example 4 7.1 0.41 0.22 0.56 0.36 0.11 0.028 0.008 - - - 0.015 - margin Comparative Example 5 7.1 0.41 0.22 0.56 0.36 0.11 0.028 0.008 - - - - - margin Comparative Example 6 8.5 0.14 0.17 0.67 0.24 0.15 0.036 - - - 0.006 0.018 0.080 margin Comparative Example 7 8.5 0.14 0.17 0.67 0.24 0.15 0.036 0.005 - 0.040 - 0.018 - margin Comparative Example 8 8.5 0.14 0.17 0.67 0.24 0.15 0.036 0.005 - - - 0.018 0.080 margin Comparative Example 9 8.5 0.14 0.17 0.67 0.24 0.15 0.036 - 0.008 - - - 0.080 margin Comparative Example 10 8.5 0.14 0.17 0.67 0.24 0.15 0.036 - - - - - - margin Comparative Example 11 7.1 0.41 0.22 0.56 0.36 0.11 0.028 0.11 0.01 0.001 0.015 0.04 0.005 margin Comparative Example 12 8.5 0.14 0.17 0.67 0.24 0.15 0.036 0.11 0.01 0.001 0.015 0.04 0.005 margin
[0113] Tensile test specimens, metallographic samples, and bending angle test specimens were prepared by sampling and cutting the casting products of Examples 1-10 and Comparative Examples 1-12. Tensile mechanical properties were tested according to GB / T 228.1 standard, metallographic structure and fracture surface were analyzed by scanning electron microscopy according to JB / T 7946.1 standard, bending angle test and fluidity test were performed according to VDA238-100 standard.
[0114] The test results are shown in Table 2.
[0115] Table 2 Mechanical properties of heat-free recycled aluminum alloys in each group
[0116]
[0117] Analysis of the mechanical property test results in Table 2 shows that when one or more of the added elements Cr, Sb, Sn, Ga, Hf, and RE are omitted, the mechanical properties and fluidity of the alloy decrease, and the bending angle becomes smaller. Comparisons between Example 3 and Comparative Examples 1-5, and Example 7 and Comparative Examples 6-10, show that when certain elements of Cr, Sb, Sn, Ga, Hf, and RE are not added to the alloy, the tensile strength, yield strength, elongation, and bending angle all decrease to varying degrees, and the alloy's fluidity deteriorates. Furthermore, comparisons between Example 3 and Comparative Example 11, and Example 7 and Comparative Example 12, indicate that when the mass percentage relationship of the alloy does not meet the range of 1 < M ≤ 2500 and 1 < N ≤ 100, the mechanical properties of the alloy decrease significantly. It is believed that the synergistic effect of different elements within the alloy has "failed" in this case. Practice shows that the mass percentage relationship of this composite design must be strictly controlled within the range described in this invention to achieve the best mechanical properties of the product.
[0118] The heat-free die-cast aluminum alloy specimens of the present invention have both high yield strength and high elongation, with flow properties comparable to AlSi10MnMg, large bending angle, and the material will not crack during riveting.
[0119] By observing the die-casting process of the embodiments, it can be seen that the heat-free aluminum alloy of the present invention does not stick to the mold during the die-casting process, and the fluidity test results are good.
[0120] Figure 1 The image shows the metallographic structure of the aluminum alloy die-cast product from Example 3. Figure 2 The image shows the metallographic structure of the product made using the aluminum alloy die-casting method of Example 5.
[0121] from Figure 1 and Figure 2 As can be seen, the α-Al grains in the metallographic structure are small and uniformly distributed, and there is no coarse pre-crystallized structure in the matrix, indicating that the alloy modification effect is good.
[0122] Figure 3 The image shows a scanning electron microscope (SEM) image of the fracture surface of the aluminum alloy die-cast product from Example 7 after it has been pulled apart.
[0123] from Figure 3 As can be seen, the dimples at the fracture surface of the sample are dense and uniform in size, which is a typical ductile fracture, indicating that the material has high strength and high toughness.
[0124] Figure 4The images show actual samples after bending angle testing of the aluminum alloy die-casting products from Examples 3, 5, and 7 (corresponding to 3501, 3502, and 3503, respectively).
[0125] Figure 5 This is a physical image of a sample after the aluminum alloy of Example 3 was tested for fluidity by die casting.
[0126] The above results indicate that the present invention, by adding trace elements Cr, Sb, Sn, Ga, Hf, and RE to the aluminum alloy in a specific ratio, optimizes the alloy's properties primarily through the synergistic effect of these different elements. This effectively improves the tensile strength, yield strength, and elongation of the aluminum alloy, significantly increases the bending angle, and maintains good flow properties.
[0127] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A high-strength, high-toughness, heat-treatable-free aluminum alloy, characterized in that, In addition to Al, the following components are also included by mass percentage: Si: 6.8-9.3wt.%, Fe: 0.1-0.41wt.%, Cu: 0.01-0.24wt.%, Mn: 0.4-0.7wt.%, Mg: 0.08-0.55wt.% , Ti: 0.06-0.18wt.%, Sr: 0.016-0.041wt.%, Cr: 0.001-0.11wt.%, Sb: 0.001-0.01wt.%, Sn: 0.0 0.01-0.05 wt.%, Ga: 0.001-0.015 wt.%, Hf: 0.01-0.04 wt.%, and RE: 0.005-0.11 wt.%, wherein the total amount of impurities does not exceed 0.2 wt.%, and M = 100 × Sn / (Cr + Sb), 1 < M ≤ 2500, and N = 10 × RE / (Ga + Hf), 1 < N ≤ 100; the RE includes one or more of La, Ce, and Gd.
2. The high-strength, high-toughness, heat-free aluminum alloy according to claim 1, characterized in that, The high-strength and high-toughness heat-free aluminum alloy, in addition to Al, also includes the following components by mass percentage: Si: 6.8-7.6wt.%, Fe: 0.36-0.41wt.%, Cu: 0.18-0.24wt.%, Mn: 0.4-0.7wt.%, Mg: 0.35-0.55wt. %, Ti: 0.06-0.18wt.%, Sr: 0.016-0.031wt.%, Cr: 0.005-0.11wt.%, Sb: 0.001-0.01wt.%, Sn: 0.0 0.01-0.035 wt.%, Ga: 0.009-0.015 wt.%, Hf: 0.01-0.04 wt.%, RE: 0.005-0.11 wt.%; wherein the total amount of impurities does not exceed 0.2 wt.%, and M = 100 × Sn / (Cr + Sb), 1 < M ≤ 2500, and N = 10 × RE / (Ga + Hf), 1 < N ≤ 100; the RE includes one or more of La, Ce, and Gd.
3. The high-strength, high-toughness, heat-free aluminum alloy according to claim 2, characterized in that, The high-strength and high-toughness heat-free aluminum alloy, in addition to Al, also includes the following components by mass percentage: The composition is as follows: Si: 7.1 wt.%, Fe: 0.41 wt.%, Cu: 0.22 wt.%, Mn: 0.56 wt.%, Mg: 0.36 wt.%, Ti: 0.11 wt.%, Sr: 0.028 wt.%, Cr: 0.008 wt.%, Sb: 0.006 wt.%, Sn: 0.02 wt.%, Ga: 0.012 wt.%, Hf: 0.015 wt.%, RE: 0.09 wt.%, wherein the total amount of impurities does not exceed 0.2 wt.%, and the RE consists of La: 40 wt.% and Ce: 60 wt.%.
4. The high-strength, high-toughness, heat-free aluminum alloy according to claim 1, characterized in that, The high-strength and high-toughness heat-free aluminum alloy, in addition to Al, also includes the following components by mass percentage: Si: 7.6-9.3wt.%, Fe: 0.1-0.35wt.%, Cu: 0.01-0.18wt.%, Mn: 0.4-0.7wt.%, Mg: 0.08-0.35wt.% , Ti: 0.06-0.18wt.%, Sr: 0.031-0.041wt.%, Cr: 0.001-0.005wt.%, Sb: 0.001-0.01wt.%, Sn: 0.0 35-0.05 wt.%, Ga: 0.001-0.009 wt.%, Hf: 0.01-0.04 wt.%, RE: 0.005-0.11 wt.%; wherein, the total amount of impurities does not exceed 0.2 wt.%, and M = 100 × Sn / (Cr + Sb), 1 < M ≤ 2500, and N = 10 × RE / (Ga + Hf), 1 < N ≤ 100; the RE includes one or more of La, Ce, and Gd.
5. The high-strength, high-toughness, heat-free aluminum alloy according to claim 4, characterized in that, The high-strength and high-toughness heat-free aluminum alloy, in addition to Al, also includes the following components by mass percentage: Si: 8.5wt.%, Fe: 0.14wt.%, Cu: 0.17wt.%, Mn: 0.67wt.%, Mg: 0.24wt.%, Ti: 0.15wt.%, Sr: 0 .036wt.%, Cr: 0.005wt.%, Sb: 0.008wt.%, Sn: 0.04wt.%, Ga: 0.006wt.%, Hf: 0.018wt.%, RE: 0.08 wt.%; wherein the total amount of impurities does not exceed 0.2 wt.%, and the RE consists of La: 50 wt.%, Ce: 40 wt.% and Gd: 10 wt.%.
6. A method for preparing a high-strength, high-toughness, heat-free aluminum alloy according to any one of claims 1 to 5, characterized in that, Includes the following steps: The raw materials are prepared according to the composition ratio of the high-strength and high-toughness heat-free aluminum alloy. All raw materials except Mg and Ga are melted, and then Mg and Ga are pressed into the melt for melting. The alloy is then successively refined and degassed, slag removed, composition detected and adjusted, and cast to obtain the high-strength and high-toughness heat-free aluminum alloy.
7. The method for preparing high-strength, high-toughness, heat-free aluminum alloy according to claim 6, characterized in that, The refining and degassing temperature is 720-740℃, and the amount of refining agent added during the process is 0.1-0.6% of the melt weight.
8. The application of the high-strength and high-toughness heat-free aluminum alloy according to any one of claims 1 to 5 in die-cast automotive parts.
9. The application according to claim 8, characterized in that, The die casting is high-pressure die casting, with a casting pressure of 350-450 bar, an injection speed of 3-6 m / s, a vacuum degree of <50 mbar, a die casting temperature of 680-720℃, and a mold temperature of 190-230℃.
Citation Information
Patent Citations
High-strength and high-toughness heat-treatment-free aluminum alloy material and preparation method thereof
CN113755722A
Non-heat-treatment reinforced high-strength and high-toughness die-casting aluminum-silicon alloy and preparation method thereof
CN114411020A
High-strength, high-toughness and high-thermal-conductivity aluminum alloy for die casting
CN109750191A
Non-heat-treated high-toughness die-casting aluminum-silicon alloy and preparation method thereof
CN114231799A
Aluminum alloy and preparation method thereof, casting and preparation method thereof, and vehicle
CN117965969A
Cited By
High-iron-content heat-treatment-free secondary aluminum-based high-pressure cast aluminum alloy and preparation method thereof
CN122038857A